The genetic diversity of trans-caucasian native sheep breeds - Hirbo, J.; Muigai, Anne W.T.; Naqvi, A.N.; Rege, J.E.O.; Hanotte, Olivier H. (2006)
The genetic variation in 10 indigenous Caucasian sheep breeds was studied with 14 micro-satellite loci in order to determine the genetic diversity among and between the breeds. Five breeds from Asia, five breeds from Europe and one breed from Africa, were included in order to study any relationships or influences they may have with the Caucasian sheep analyzed. A Karakul population from Uzbekistan was included in the study to see whether there was any Central Asian influence. All the 14 loci were found to be polymorphic in all the breeds, with the exception of ILST0056, which was monomorphic in Imeretian. A total of 231 alleles were generated from all the 688 individuals of the sheep analyzed. The mean number of alleles (MNA) at each locus was 16.5. The total number of alleles detected in all samples ranged from 13 in several loci to 23 in OarJMP029. Out of total 308 Hardy-Weinberg Equilibrium (HWE) tests, 85 gave significant results. After Bonferroni correction for multiple tests, 30 comparisons still remained significant to the experimental levels. The Gala population was the most diverse and Imeretian the least diverse with a MNA of 8.50 and 5.51, respectively. Gene diversity estimates exhibited the same trend and ranged from 0.803 in Gala and 0.623 in Imeretian, but generally there is higher diversity among the Caucasian breeds in comparison to other eference breeds. The closest breeds were Tushin and Bozakh with Da of 0.113 and most distant breeds were Djallonk챕 and North Rondalsy with Da of 0.445. Principal Component (PC) analyses were done. PC1 described 14% of the differences. PC2, which described 13% of the differences, further separated the Caucasian breeds from Asian breeds except Karakul and Awasi, and the two British breeds. PC3 described 10% of the differences, allowing better differentiation of the Caucasian breeds. A moderate degree of reliability was observed for individual-breed assignment from the 14 loci using different approaches among which the Bayesian method proved to be the most efficient. About 72% of individuals analyzed were correctly assigned to their respective breeds.